Population trend and ecology of the most isolated deer in the world, Bawean deer (Axis kuhlii): conservation challenges - Rahman, Dede Aulia; Aulagnier, Stéphane; Sunderland-Groves, Jacqueline L.; Semiadi, Gono (THERYA, 2023)
The Bawean deer plays a vital role in its small and isolated ecosystem as a herbivore and effective seed disperser, as well as holds cultural importance to the local community. However, the ecology of this Critically Endangered deer is poorly studied. Using random encounter and occupancy modeling based on 29,350 camera trap days between 2017 and 2019, we aimed to provide population estimates, habitat preferences, and behavioral data for this species. The population was 120–277 mature individuals, much less than the number in 1978. The density of Bawean deer could be related to the type of forest and the predation by free-roaming dogs as well as other factors such as the increase of wild pigs on Bawean Island. According to the best occupancy model, the tall and community forests far from human settlements are the most suitable areas for this species. Bawean deer is mainly crepuscular with significant daytime activity. Our results point out free-roaming dogs as a major threat to the native mammal community on Bawean island. We suggest the Bawean deer be listed as Critically Endangered following criteria B1a,b (ii, iii, v) of IUCN. Therefore, effective law enforcement and an adequate conservation strategy, including free-roaming dog control, are required to reduce the impacts of both direct and indirect threats.